Ascertain Quality Attributes for Design and Development of New Improved Chatbots to Assess Customer Satisfaction Index (CSI): A Preliminary Study - Johari, Nurul Muizzah; Zaman, Halimah Badioze; Nohuddin, Puteri N. E. (Advances in Visual Informatics, 2019)
Chatbots are artificial intelligence applications that are used as tools to communicate and assist humans in any task designed. It uses knowledge that has been provided by the developer and continue to learn on its own through a Natural Language Processing (NLP) approach. This paper highlights a study that aims to investigate quality attributes for a new improved Chatbots to assess customer satisfaction. The preliminary study was conducted to acquire prior understanding on the characteristics and functionalities capable of Chatbots to capture potential customer satisfaction in the tourism domain before a prototype is developed. The findings from this study reveal seven (7) plausible dimensions with several sub-factors of quality attributes that can be applied to new improved Chatbots. These dimensions and sub-factors are useful inputs to the Systems Requirement Specifications (SRS) for the design and development of new improved Chatbots to assess Customer Satisfaction Index (CSI).